Comparative Pharmacoeconomic Study of Proton Pump Inhibitors in Gastritis Treatment Using Cost Minimization Approach - Hakim, Reny Anggriany; Hadiq, Shabran; Jannah, Raudhatul; Umi, Sri (Journal of Pharmaceutical and Health Research, 2025)
Gastritis is an inflammatory condition of the gastric mucosa with varying degrees of severity, ranging from mild asymptomatic cases to more severe forms associated with significant morbidity. The condition may be influenced by multiple factors, including dietary habits that stimulate gastric acid secretion, irregular eating patterns, infections, psychological stress, alcohol consumption, and the use of certain medications such as nonsteroidal anti-inflammatory drugs and corticosteroids. Cost Minimization Analysis (CMA) is a pharmacoeconomic approach applied to compare therapeutic alternatives that have equivalent clinical effectiveness by identifying the option with the lowest direct medical cost. Meanwhile, studies examining real-world cost efficiency at the level of primary care services or private community pharmacies remain relatively limited and underreported. Therefore, this study aims to analyze the cost of PPI use in gastritis patients at Fella Farma Pharmacy in 2023 using the Cost Minimization Analysis (CMA) approach. The results of this study are expected to determine PPI alternatives with the lowest therapy costs as a basis for decision-making in more efficient and rational pharmaceutical services. This study conceptualizes that the use of proton pump inhibitors, specifically omeprazole and lansoprazole, influences the total therapy costs incurred by patients. The choice of PPI is assumed to affect overall treatment expenses as reflected in retrospective medical record data from Fella Farma Pharmacy in 2023. This study used a quantitative research design with retrospective data collection using medical records obtained from Fella Farma Pharmacy for the year 2023.A sample of 52 patients who met the inclusion and exclusion criteria at the Fella Farma Clinical Pharmacy in 2023. The data obtained were then analyzed for minimum costs to determine the lowest cost of treatment between Omeprazole (patent brand x) and Lansoprazole (patent brand y). The results of the study showed that the use of Proton Pump Inhibitor (PPI) drugs that had the lowest cost was omeprazole with an average total cost of IDR 351,000/patient compared to lansoprazole with an average total cost of IDR 514,000/patient.